Classroom Management Training for Teachers at SIT Makassar Islamic School - Abubakar, Multazam; Azhar, Sophia; Zulqaidah, Ulfa; Mildayanti; Nur Afifah; Mutmainna (IJOCSE: Indonesian Journal of Community Services, 2023)
Classroom Management training aims to improve the ability of teachers to create conducive classroom conditions so that learning objectives can be achieved optimally. This Classroom Management training is expected to be able to improve the ability of TKIT and SDIT Makassar Islamic School teachers in managing classes for more effective learning. Apart from Classroom Management, Makassar Islamic School management also routinely conducts other trainings to improve teachers’ abilities in various fields. In this training material, Mr. Ucha conveyed the steps to create a fun class, starting from starting class, check-in, check-out, signals, appreciation, grab attention, grouping, ice breaking, to closing with songs and movements to improve students’ interest in learning and also explaining the teacher’s role in the classroom, one of which is as a facilitator who helps students gain their own understanding of the material, provides an active role for students in the classroom, and motivates students.